Effect of Fat Substitution on the Rheological and Textural Properties of Raw Chicken Meat Emulsion and Cooked Patties - Chappalwar, Anita; Pathak, Vikas; Goswami, Meena; Verma, Arun Kumar; kumar, V. Raj (Journal of Meat Science, 2023)
The present study was conducted to evaluate the rheological behaviour and textural properties of raw chicken meat emulsion and cooked patties respectively. Low fat chicken emulsions were prepared with the addition of pre-optimized levels of 1%lemon albedo, 2% mango peel powder, and 2% banana peel powder with the replacement of 50% vegetable oil in formulation The rheological behaviour of low fat emulsion and textural properties of these low fat emulsion based chicken patties were observed. The formulation of chicken meat emulsion was maintained by the addition of water with the replacement of fat. Dynamic oscillatory measurements revealed the weak gel formation of emulsions with addition of fat replacers, as storage modulus values (G΄) were higher than the loss modulus values (G˝). Chicken meat patties were prepared from these low fat chicken meat emulsions. Textual profile analysis of cooked patties showed a significant (P<0.05) effect on hardness, fracturability, cohesiveness, gumminess, and chewiness values. Therefore, it was concluded that replacement of fat with optimum level natural fat replacers (lemon albedo, mango peel powder and banana peel powder) resulted in predominant visco-elastic behaviour of emulsions which in turn had a significant effect on textural properties of the emulsion. Hence, the visco elastic behaviour of emulsion and the effect of textural properties might improve the acceptability of cooked low fat chicken patties.